A Survey of Knowledge, Attitude and Practice of Iranian Dentists and Pedodontists in Relation to Child Abuse - Fatemeh Jahanimoghadam; Mahsa Kalantari; Azadeh Horri; Habibeh Ahmadipour; Ehsan Pourmorteza (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Since almost half of the child abuse cases affect the head and neck region, dentists have an important role in the diagnosis and report of oral and dental aspects of child abuse cases. Purpose: The objective of the current study was to evaluate the knowledge, attitude and practice of the general dentists and pedodontists regarding child abuse and child neglect. Materials and Method: This cross-sectional study was carried out on the participants of the 12th congress of pedodontists of Iran. A self-administered questionnaire was used for evaluating their knowledge, attitude and practice toward child abuse. T-test and ANOVA were applied to analyze the data by SPSS software. p <0.05 was considered statistically significant. Results: The mean score of knowledge, attitude and practice of the participants regarding child abuse was 10.24±2.68, 41.54±11.24 and 2.78±1.05, respectively. The knowledge of pedodontists was significantly higher than knowledge of general dentists. No statistically significant difference was observed in attitude and practice (p> 0.05). Conclusion: Dentists had a moderate knowledge, poor attitude and moderate practice regarding child abuse. Considering this fact, improvements in child abuse education for undergraduate students and continuing post-graduate training in this field are recommended.